Affixation in the Album Kalangkang by Nining Meida - Nurulita, Dwi Hasna; Kadir, Puspa Mirani; Wagiati, NFN (Balai Bahasa Kalimantan Tengah, 2024)
This research examines affixations in the album Kalangkang using qualitative methods. The data used was taken from the lyrics of Nining Meida's song on the album Kalangkang on the internet site. The results of the research show that from 110 data, 36 prefixes were found, namely the prefixes di-, ka-, mi-, nga-, pa-, nasal (n-, ng-, ny-) predominantly indicating adjectives, 6 data infixes, namely The infixes -um-, -ar-, -al-, predominantly indicate adjectives and plurals. There are 26 data suffixes, namely the suffixes -na, -an, -eun, which are often found in remake songs because the lyrics are in the form of sampirans, pantuns and old poetry, so the suffixes play an important role in adapting the rhyme. There are 24 affix combinations of data, namely prefix+infix, prefix+suffix predominantly indicating adjectives. The affixed and nasal reduplications of 12 data consisting of affixed dwipure, affixed dwipurwa, and affixed dwipurwa predominantly form verbs. There are typical characteristics of Sundanese affixations, including: The prefix ka- has the function of indicating adjectives and verbs and predominantly has an accidental meaning. Apart from that, infixes in Sundanese predominantly indicate plural numbers. The combination of the affix in Sundanese forms its own meaning, namely 'most', reduplication in Sundanese for example, dwipurwa with the affix is a partial repetition where the word being repeated is the first syllable of the word.AbstrakPenelitian ini mengkaji afiks dalam album Kalangkang dengan menggunakan metode kualitatif. Data yang digunakan diambil dari lirik lagu Nining Meida pada album Kalangkang pada situs internet. Hasil penelitian menunjukkan dari 110 data, ditemukan prefiks sebanyak 36 data yaitu prefiks di-, ka-, mi-, nga-, pa-, nasal (n-, ng-, ny-) didominasi menunjukkan kata sifat, Infiks sebanyak 6 data, yaitu infiks -um-, -ar-, -al-, didominasi menunjukkan kata sifat dan jamak. Sufiks sebanyak 26 data, yaitu sufiks -na, -an, -eun, banyak ditemukan dalam lagu remake karena liriknya berupa sampiran, pantun, dan puisi lama., sehingga sufiks berperan penting untuk menyesuaikan rima. Kombinasi afiks sebanyak 24 data, yaitu prefiks+infiks, prefiks+sufiks didominasi menunjukkan kata sifat. Reduplikasi berafiks dan bernasal sebanyak 12 data yang terdiri atas dwimurni berafiks, dwireka berafiks, dan dwipurwa berafiks didominasi membentuk kata kerja. Terdapat ciri khas afiksasi bahasa Sunda, di antaranya prefiks ka- memiliki fungsi menunjukkan adjektiva dan kata kerja dan didominasi memiliki makna ketidaksengajaan. Selain itu, infiks dalam bahasa Sunda didominasi jumlah jamak. Kombinasi afiks pang- + -na dalam bahasa Sunda membentuk makna tersendiri, yaitu ‘paling’, reduplikasi bahasa Sunda misalnya, dwipurwa berafiks merupakan pengulangan sebagian dan kata yang diulang merupakan suku kata pertama kata tersebut.